KONSTRUKSI KEBIJAKAN DESENTRALISASI FISKAL BERBASIS PARADIGMA GOOD FINANCIAL GOVERNANCE DI INDONESIA - Nirwan Ardhi Jaya (Humani (Hukum dan Masyarakat Madani), 2020)
Fiscal decentralization policy has deviated from the main objective and abused a lot. Fiscal decentralization policy should be implemented based on the Paradigm of Good Financial Management (good financial governance) in order to realize the country's goals to advance the people's welfare. The purpose of this study, namely; to find out and analyze the importance of fiscal decentralization policies based on the paradigm of Good Financial Governance in Indonesia. The research method used was a qualitative method, with a normative juridical approach and presented in an analytical descriptive form. The construction of fiscal decentralization policies based on the paradigm of Good Financial Governance in Indonesia, is carried out with at least the application of 3 (three) basic principles, namely; minimum service system, money follow function and performance based budget, to realize financial management that obeys the rule of law, transparency and participation. The integration of the paradigm of good financial governance in the implementation of fiscal decentralization policies must be supported by budgeting politics that policy makers, in order to accelerate the realization of the value of usefulness (usefulness). The government is expected to conduct philosophical, juridical and sociological studies of various regulations concerning the management of state and regional finances in preparation for applying the paradigm of good financial governance as a guide to the financial management process.